2019
DOI: 10.1590/1806-9061-2019-0980
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Anatomy of Hepatic and Portal Veins with Special Reference to Biliary Duct System in Broiler Chickens (Gallus gallus domesticus): A Recent Illustration

Abstract: Chickens have a great participation in meat and egg production. The anatomical scientific data of poultry is important to support the recent researches either for illustrations in academic studies or clinically in diagnosis and treatment of some poultry nutritional diseases. The current investigation was performed on twenty broiler chickens of both sexes. The chickens were anaesthetized, slaughtered then the venous system was flushed with a normal saline to anatomically investigate the distribution of hepatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 12 publications
2
9
1
Order By: Relevance
“…On the other hand, our results showed that the liver, which is the largest gland in the endocrine system, increased its absolute weight by 4.59 g in the first 10 days of life ( Figure 1 ). This organ (liver) participates in the metabolism of proteins, carbohydrates, and lipids [ 20 ], thus an increase of the absolute liver weight in apparently healthy young birds has been related to a higher functional activity of the organ, which is essential for the assimilation of nutrients in the early stages [ 19 , 20 ]. Likewise, due to its exocrine and endocrine function [ 20 ], the pancreas increases its absolute weight (0.85 g; Figure 1 ) according to the age of the chickens, with the highest absolute values on days 9 and 10 of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our results showed that the liver, which is the largest gland in the endocrine system, increased its absolute weight by 4.59 g in the first 10 days of life ( Figure 1 ). This organ (liver) participates in the metabolism of proteins, carbohydrates, and lipids [ 20 ], thus an increase of the absolute liver weight in apparently healthy young birds has been related to a higher functional activity of the organ, which is essential for the assimilation of nutrients in the early stages [ 19 , 20 ]. Likewise, due to its exocrine and endocrine function [ 20 ], the pancreas increases its absolute weight (0.85 g; Figure 1 ) according to the age of the chickens, with the highest absolute values on days 9 and 10 of life.…”
Section: Discussionmentioning
confidence: 99%
“…This organ (liver) participates in the metabolism of proteins, carbohydrates, and lipids [ 20 ], thus an increase of the absolute liver weight in apparently healthy young birds has been related to a higher functional activity of the organ, which is essential for the assimilation of nutrients in the early stages [ 19 , 20 ]. Likewise, due to its exocrine and endocrine function [ 20 ], the pancreas increases its absolute weight (0.85 g; Figure 1 ) according to the age of the chickens, with the highest absolute values on days 9 and 10 of life. These results contribute to understanding irregularities in the absolute weight and possible activity of the digestive tract by observing drastic changes, confirming that the first 10 days are the most critical of the bird.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatic carrier system in ostriches (S. camelus) is formed by the union of the right and left hepatic vein, similar to the case in G. gallus (17,18,19) , in ducks (C. moschata) (13,14) , in geese (A. domestica) (13), in domestic pigeons (C. livia domestica) (13,15,26), in egret (B. ibis)( 16) , in duck (Anas anas domesticus) and domestic goose (Anser anser domesticus) (22). However, in geese (A. domestica) and ducks (C. moschata) (23) the hepatic carrier system is formed by two left and one right hepatic carrier veins.…”
Section: Discussionmentioning
confidence: 87%
“…In the ostrich, the left hepatic vein drains the proventricle through the ventral and left proventriculosplenic veins and part of the gastric ventricle through the gastric veins as in G. gallus (17,18,19) , in the egret (B. ibis) (16) and in domestic pigeons (C. livia domestica) (13,15) . In G. gallus (17,18,19,26) , the left hepatic vein is formed by the ventral and left gastric veins and by the proventricular veins (13) . Conversely, in ducks, the left hepatic vein is formed by one or two left gastric veins that drain blood from the ventral margin of the gastric ventricle, in addition to the pyloric and caudal proventricular veins (19) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation